Development and Improvement Of Approaches to The Diagnosis and Treatment Of Inflammatory Diseases Of The Temporomandibular Joint - Safarova Mashkhura Sulaymonovna; Khаmitоvа Firuzа Аrtуkоvnа (Indonesian Journal Publisher, 2025)
This study aims to improve diagnostic and treatment approaches for inflammatory diseases of the temporomandibular joint (TMJ), which significantly impact patients' quality of life. A total of 245 patients aged 18-55 and older were clinically examined between 2020 and 2024 to identify the most effective treatment methods. The study used clinical, radiographic, and laboratory evaluations to assess the condition of the articular head and disc. Findings revealed that 70-80% of TMJ cases involved soft tissue pathologies, such as articular disc and ligament dysfunctions, with arthritis and osteoarthritis risk increasing with age. Patients commonly experienced intense headaches, ear pain, limited mouth opening, and joint noises. Treatment involved osteotropic antibiotic injections, analgesics, and enzyme electrophoresis, showing significant improvements in joint mobility and pain reduction. The study highlights the importance of early diagnosis, tailored treatment plans, and a multidisciplinary approach to managing TMJ disorders. Implementing optimized diagnostic techniques and individualized therapy can enhance patient outcomes and prevent disease progression.